Anxiety and depression in patients with post-COVID-19 comorbities: Post-COVID: Anxiety and Depression - R. da Rocha, Maria Debora; T. N. D. Rodrigues, Isabeli; C. Santos, Sandra Virgínia; P. Santos, Thalyta Cibele; S. Santos, Pammela Weryka; C. Gomes, Paulo Roberto; A. Hazime, Fuad; S. Cardoso, Vinicius (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The COVID-19 pandemic has brought significant impacts on mental health, increasing conditions such as anxiety and depression. The negative impact was even bigger among the population with chronic illnesses like diabetes, hypertension, and obesity. Fear of contamination, social isolation, lack of medical follow-up, and changes in lifestyle have contributed to the worsening of these disorders. Objective: The aim of this study was to assess anxiety and depression levels and quality of life in individuals with pre-existing comorbidities post COVID-19. Methods: This is a cross-sectional study with a descriptive and analytical approach. The study included 125 individuals divided in healthy group and chronically ill group. Behavioral and clinical characteristics were evaluated, such as physical activity after COVID-19, smoking, alcohol consumption, pre-existing comorbidities, and symptoms of anxiety and depression. Results: The study highlighted that the patients with diabetes and hypertension suffered the most from anxiety and depression possibly due to the higher susceptibility to coronavirus infection and the negative impact of these pre-existing conditions on mental health. In hypertensive individuals, the complex interaction between emotional stress, anxiety, and cardiovascular system dysregulation contributed to increased levels of anxiety and depression. Obesity, besides a risk factor for severe COVID-19, it also negatively impacted the immune system and had adverse effects on mental health, with an increase in depressive and anxious symptoms. Conclusion: This study emphasizes the need of special care to at-risk groups to minimize adverse impacts on mental health and improve the quality of life of individuals with pre-existing comorbidities post COVID-19.